Une réhabilitation naturaliste de Machiavel - Jean-Pierre Cavaillé (Les Dossiers du GRIHL)
Thearticle attempts tosummarizeMachon’s theoretical approach – surprising, to say the least–, in his Apologyof Machiavelli,thepolitical writerundoubtedlythe mostdecriedof his time.Machonasserts that he wantsto showthe compatibility of thedoctrineof MachiavelliwithChristianpietyand morality, but he strives todefend the"maxims" attributed toMachiavelli whichare considered the mostindefensible, the mosttransgressive for Christianity.Insteadof challenging theletter and the spiritof thesemaximsassigned toMachiavelli byanti-Machiavellists, he reinsertsfirst them in the works ofMachiavelli,whichhe quotesextensively inItalian and then in French. The approach is, however, not philologicalbutpolitical;it aims atdefendingexplicitlyeverything which is plainly andirremediablyoutrageous within the political theory ofMachiavelli.This defenseis based on thenotionsof necessity andusefulness within the contextof a fundamentallynaturalistic theory ofreason of state, whichisconsidered asuniversal; Machon’s feat, truly amazing, consists in the assertion that Christian writers, beginning with the Bibleitself,obey to the iron rules of policydictated by nature.